Analisis Kinerja Keuangan Menggunakan Metode Economic Value Added (EVA) Pada PT. Data Sinergitama Jaya, Tbk - Risna, Risna; Rahma, Agussalim; Masmarulan, Masmarulan (Khazanah Journal: Economics, Muamalah & Entrepreneurship, 2024)
This research aims to determine the financial performance of PT. Data from Sinergitama Jaya, Tbk. The method or type of research used in this writing is quantitative data. The data source used in this research is secondary data. The research population which is also the research sample is the financial reports for the last two years (2022-2023). This research uses EVA analysis which consists of NOPAT and Invested Capital analysis and WACC and Cost of Capital. The results of this research show that the Economic Value Added (EVA) value at PT. Data from Sinergitama Jaya, Tbk. In 2022 to 2023, the EVA value < 0 or EVA is negative, this is because the operating profit is smaller than the capital costs incurred, which means that PT. Data from Sinergitama Jaya, Tbk. failed to meet the expectations of creditors and shareholders and failed to create added economic value for the company.